2016
DOI: 10.3390/v8100296
|View full text |Cite
|
Sign up to set email alerts
|

Griffithsin: An Antiviral Lectin with Outstanding Therapeutic Potential

Abstract: Griffithsin (GRFT), an algae-derived lectin, is one of the most potent viral entry inhibitors discovered to date. It is currently being developed as a microbicide with broad-spectrum activity against several enveloped viruses. GRFT can inhibit human immunodeficiency virus (HIV) infection at picomolar concentrations, surpassing the ability of most anti-HIV agents. The potential to inhibit other viruses as well as parasites has also been demonstrated. Griffithsin’s antiviral activity stems from its ability to bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
115
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(120 citation statements)
references
References 54 publications
0
115
1
4
Order By: Relevance
“…Among non-legume lectins, griffithsin (GRFT), cyanovirin (CV-N) and banana lectin (BanLec) (Swanson et al, 2010) are known to have antiviral effect. Very often, these lectins are incorporated into vaginal and rectal gels, creams and suppositories to prevent HIV transmission (Lusvarghi and Bewley, 2016). Here, lectins bind viruses and block their entry and fusion to target cells by averting infection.…”
Section: Antiviral Activity Of Lectinsmentioning
confidence: 99%
“…Among non-legume lectins, griffithsin (GRFT), cyanovirin (CV-N) and banana lectin (BanLec) (Swanson et al, 2010) are known to have antiviral effect. Very often, these lectins are incorporated into vaginal and rectal gels, creams and suppositories to prevent HIV transmission (Lusvarghi and Bewley, 2016). Here, lectins bind viruses and block their entry and fusion to target cells by averting infection.…”
Section: Antiviral Activity Of Lectinsmentioning
confidence: 99%
“…CD4 binding induces changes in gp120 resulting in the exposure of envelope domains, which were previously hidden at the moment it binds to the host cells. 33 Interestingly, several lectins with anti-HIV activity show recognition of different carbohydrates. It is difficult for antibodies to reach the initiallyuncovered surface protein domains efficiently, which also means that efficient vaccines are not available yet for HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Such uncovered domains may then bind to the CXCR4 or CCR5 co-receptors on the cell membrane. 31,34 Griffithsin binds to mannose/glucose structures, cyanovirin N predominantly binds to alphaIJ1,2)-mannose structures, Galanthus nivalis agglutinin (GNA) and Hippeastrum hybrid agglutinin exhibit α(1,3)/α(1,6)-mannose-binding activity 33 and Musa acuminata agglutinin (BanLec) binds to high mannose carbohydrate structures. 31 The HIV surface glycoprotein gp120 is one of the most heavily glycosylated proteins known so far, and its molecular weight consists of ∼50% of glycans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Griffithsin, a protein from red seaweeds, is another drug with the same mechanism of action. Studies to date are encouraging, as they have demonstrated its activity in picomolar concentrations and absence of irritability and inflammation 60,61. It has also been successfully expressed and purified from transgenic plants, which would make it more economical 60,6264.…”
Section: Historical Development Of Vaginal Microbicidesmentioning
confidence: 98%